Kebijakan ODA Melalui JICA dalam Pembangunan MRT di Jakarta - Dhedhe Naomi; Esyana Oktaviani; Lycael M. Telussa; Setiorini Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
The construction of Mass Rapid Transit (MRT) is one of the strategic measures to address urban transportation problems, such as congestion and limited mobility. The Official Development Assistance (ODA) policy channeled through the Japan International Cooperation Agency (JICA) plays an important role in supporting this project, both in financial and technical terms. This study aims to analyze the contribution of ODA policy in the development of Jakarta MRT, particularly its impact on improving transportation infrastructure, economic growth, and environmental quality. The research method used is a qualitative approach with secondary data analysis from official documents, reports, and related studies. The result shows that the policy of Official Development Assistance (ODA) through JICA in the construction of MRT Jakarta has significantly contributed to the improvement of transportation infrastructure, congestion reduction, and economic growth. The technical and financial support from JICA enables Indonesia to utilize Japanese technology to create a sustainable transportation system.